Dampak Pembangunan Ibu Kota Nusantara (IKN) sebagai Katalisator Perekonomian Regional: Pendekatan IRIO: Institut Pertanian Bogor - Mutiara Probokawuryan; Sane Pratinda, Wildan Nur Arrasyiid; Azijah, Zulva; Amaliah, Syarifah; Zain, Salma Luthfia; Nur’aeni, Aisyah (Jurnal Ekonomi dan Kebijakan Pembangunan, 2025)
Economic disparities between regions in Indonesia remain one of the main challenges in the national development process. The development of the National Capital City (IKN) is seen as an effort to create a new economic growth center outside Java Island to reduce regional economic inequality. This study aims to analyze the impact of investment in IKN development on the national economy using the Indonesian Inter-Regional Input-Output (IRIO) approach, particularly to assess its effects on economic output, household income, and employment absorption. The analysis method used is the 2016 Indonesian Inter-Regional Input-Output (IRIO) model. The findings indicate that increased government investment in IKN development, particularly in the construction sector, has a significant impact on East Kalimantan but also generates output effects in other regions, such as Jakarta, East Java, North Kalimantan, and West Java. Meanwhile, income and labor impacts are also observed in Java Island, Sulawesi Island, Sumatra Island, and partially in Balinusra (Bali-Nusa Tenggara), as well as Maluku and Papua. It is necessary to strengthen economic diversification policies and support for related sectors outside Kalimantan in order to broaden the nationwide spillover effects of the IKN development.